Redesenho dos conteúdos programáticos da disciplina de citologia e genética para ambientes virtuais. Estudo de caso baseado no programa de desenvolvimento de competências para professores universitários - Carhuaricra Meza, Julio César (2022)
The inquiry exhibits the effect of the process and the threads of diagnosis, improvement, redesign of the syllabus, and the virtualization of the cytology and genetics subject corresponding to the fifth semester of the Biology and Chemistry Study Program; Faculty of Education Sciences; National University Daniel Alcides Carrión. The applied methodology corresponded to the method, systemic - qualitative, focused on the case study; techniques, process analysis, risks, content and skills. Whose instruments were: map of processes and risks, documentary checklist with nine sections for diagnosis; assessment scale with four categories of analysis: prior to the start (1), at the start (2), in process (3) and satisfactory (4) for the redesign and adaptation in perspective of the competency-based approach and quality assurance; teaching-learning process guide for the training course: Teaching competence development program, both synchronous (Webinars) and asynchronous (Forums). And the classroom platform for virtualization. All validated by expert judgment of the Institute of Higher Education of Latin America and the Caribbean attached to UNESCO. It has been found that 04 components of the syllabus in category 3, in process: summary, skills, learning outcomes and methodology; category 2, initially: planning of learning units, evaluation; category 1, prior to the start: tutoring and category 4, satisfactory: the general data. Facts, which were improved and aligned taking into account the IESALC-UNESCO proposal for the virtualization of courses and quality assurance. In conclusion, the redesign of the syllabus of the cytology and genetics subject has been carried out considering the competency-based approach, quality and virtual environments.